Overcoming multidrug-resistant bacteria and fungi by green synthesis of AgNPs using Nepeta pogonosperma extract, optimization, characterization and evaluation of antibacterial and antifungal effects - Ebrahimzadeh, Mohammad Ali; Barani, Amin; Habibian, Amir Hossein; Goli, Hamid Reza; Alizadeh, Seyedeh Roya (European Journal of Chemistry, 2023)
This study explained a green synthesis of silver nanoparticles (AgNPs) using Nepeta pogonosperma extract and evaluated their antibacterial activity. Optimization of the temperature, concentration, pH, and reaction time was established to produce silver nanoparticles. The best condition was 10 mM AgNO3, pH = 14, temperature 85 °C, and reaction time 24 hours. The formation of silver nanoparticles was confirmed by colour-changing, UV-vis, FE-SEM, EDX, XRD, FT-IR, and DLS analysis. The prepared AgNPs had a spherical shape with an average size of 51.21±0.02 nm. In addition, our biofabricated nanoparticles displayed potential antibacterial activity against the tested strains. The MIC value of 1.17 µg/mL was determined against strains of Pseudomonas aeruginosa, Acinetobacter baumannii, and Escherichia coli and 2.34 µg/mL against Staphylococcus aureus, Klebsiella pneumoniae, Proteus mirabilis and Enterococcus faecalis. Furthermore, AgNPs exhibited excellent antifungal effects against Candida albicans strains (0.073 μg/mL). In general, N. pogonosperma played an important role in reducing Ag(+1) to Ag(0) and the production of Ag(0) with suitable surface features in combination with efficient biological activities.